Heavy metals in road dust from typical old industrial areas of Wuhan: Seasonal distribution and bioaccessibility-based health risk assessment - Liu Yuanyuan (Open Chemistry)
Heavy metals (HMs) in urban road dust could cause human health risk through potential pathways, especially in industrial areas. To identify pollution sources and propose countermeasures, the seasonal distribution of five HMs (Cu, Cr, Zn, Pb, and Cd) were analyzed from 27 sites of Qingshan Industrial District (QSD) and their induced human health risk was assessed using a developed bioaccessibility-based risk assessment model. Results showed that: (1) The concentrations of five HMs were Zn > Cr > Pb > Cu > Cd. Compared with the background values of each element, the dust enrichment capacity in summer was Zn > Pb > Cd > Cu > Cr, and in winter was Cd > Zn > Pb > Cu > Cr. (2) There was no non-carcinogenic risk in road dust in QSD and children’s total non-carcinogenic risk was higher than adults. The non-carcinogenic exposure of each HM was ingested > dermal contact > respiratory inhalation. (3) Cu-Zn-Pb-Cd mainly came from the combined pollution of traffic and industry, and Cr came from the pollution of the steel industry and natural sources. (4) Based on the assessment results, Cr, Zn, Pb, and Cd were determined as the priority control HMs.